Necesidades de apoyos en adultos con discapacidad intelectual institucionalizados: estudio en el contexto chileno (2012)
This study examines the support needs of a sample of 285 institutionalized adults with intellectual disabilities. The instrument used was the Supports Intensity Scale SIS. The results revealed the existence of low support needs, with more elevated needs in lifelong learning activities and less in home living domains. Years institutionalized and age were not associated with the level of support needs, but the severity of the disability and the gender were. These results support the cross-cultural validity of the SIS and its usefulness for planning services oriented to improving the lives of institutionalized population with intellectual disabilities.